A priori error estimates for finite volume element approximations to second order linear hyperbolic integro-differential equations - Samir Karaa (2018)
© 2015 Institute for Scientific Computing and Information. In this paper, both semidiscrete and completely discrete finite volume element methods (FVEMs) are analyzed for approximating solutions of a class of linear hyperbolic integro-differential equations in a two-dimensional convex polygonal domain. The effect of numerical quadrature is also examined. In the semidiscrete case, optimal error estimates in L∞(L2) and L∞(H1) norms are shown to hold with minimal regularity assumptions on the initial data, whereas quasi-optimal estimate is derived in L∞(L∞) norm under higher regularity on the data. Based on a second order explicit method in time, a completely discrete scheme is examined and optimal error estimates are established with a mild condition on the space and time discretizing parameters. Finally, some numerical experiments are conducted which confirm the theoretical order of convergence.